MOTIVASI KERJA MEMEDIASI PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS UMKM MASYARAKAT PESISIR SURABAYA - Mochamad Mochklas; Dwi Songgo Panggayudi; Nurullaili Mauliddah; Tyasha Ayu Melynda Sari; Rina Maretasari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
The development of MSMEs in coastal communities needs to be fostered and developed so that they can contribute to the economy of the family and the country. MSMEs productivity is an indicator that determines how efficiently MSMEs can run their business. This study aims to analyze the effect of training and work motivation on the productivity of MSMEs in coastal communities. This research method uses a quantitative method, where the population is MSMEs in the Bulak District area of Surabaya, based on the sample criteria the number of samples used in this study were 90 MSME actors. Incoming and appropriate data is processed and analyzed using SEM PLS. This study found that training and work motivation had a significant effect on increasing the productivity of MSMEs in coastal communities and work motivation mediated the effect of training on the productivity of MSMEs in coastal communities. To increase the productivity of MSMEs in coastal communities, they need to be equipped with knowledge and skills through training. The training program must be in accordance with the characteristics of MSMEs in coastal communities, so that the results of the training will motivate MSMEs in coastal communities to become independent, professional and competitive entrepreneurs.